2015
DOI: 10.1167/iovs.15-16910
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Recessive Bestrophinopathy Is Not Associated With the Loss of Bestrophin-1 Anion Channel Function in a Patient With a NovelBEST1Mutation

Abstract: Citation: Johnson AA, Bachman LA, Gilles BJ, et al. Autosomal recessive bestrophinopathy is not associated with the loss of bestrophin-1 anion channel function in a patient with a novel BEST1 mutation. Invest Ophthalmol Vis Sci. 2015;56:4619-4630. DOI:10.1167/iovs.15-16910 PURPOSE. Mutations in BEST1, encoding bestrophin-1 (Best1), cause autosomal recessive bestrophinopathy (ARB). Encoding bestrophin-1 is a pentameric anion channel localized to the basolateral plasma membrane of the RPE. Here, we character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 48 publications
(97 reference statements)
4
50
1
Order By: Relevance
“…An individual with ARB has been reported with p.R141H and p.D312N (Boon et al, 2013); as discussed above for p.R141H, p.D312N can either be asymptomatic in carriers or act dominantly in individuals with Best disease (Burgess et al, 2008; Sodi et al, 2011), giving the situation where two autosomal dominant mutations occur as compound heterozygous mutations to cause an autosomal recessive disease. Similar confounding combinations with p.R141H have also been reported with p.L41P, p.Y29X, p.P233A and p.I266fsX18 (Burgess et al, 2008; Schatz et al, 2006; Wittström et al, 2011; Johnson et al, 2015). Thus, it would seem that the pathogenic mechanism not only varies from mutation to mutation, but also on what other mutation is present and as-yet-unidentified factors such as promoter strength, modifying genes and environment.…”
Section: Discussionsupporting
confidence: 81%
“…An individual with ARB has been reported with p.R141H and p.D312N (Boon et al, 2013); as discussed above for p.R141H, p.D312N can either be asymptomatic in carriers or act dominantly in individuals with Best disease (Burgess et al, 2008; Sodi et al, 2011), giving the situation where two autosomal dominant mutations occur as compound heterozygous mutations to cause an autosomal recessive disease. Similar confounding combinations with p.R141H have also been reported with p.L41P, p.Y29X, p.P233A and p.I266fsX18 (Burgess et al, 2008; Schatz et al, 2006; Wittström et al, 2011; Johnson et al, 2015). Thus, it would seem that the pathogenic mechanism not only varies from mutation to mutation, but also on what other mutation is present and as-yet-unidentified factors such as promoter strength, modifying genes and environment.…”
Section: Discussionsupporting
confidence: 81%
“…Immunohistochemical staining of macaque and porcine eyes showed that this staining was unique to the basolateral plasma membrane and this was confirmed by confocal microscopy (Marmorstein et al, 2000). This RPE-specific ocular expression and/or basolateral plasma membrane localization of Best1 has been confirmed by many subsequent studies using several different native models, including fetal human RPE cells (Johnson et al, 2013; Marmorstein et al, 2015), induced pluripotent stem cell (iPSC)-derived RPE cells (Brandl et al, 2014; Johnson et al, 2015; Milenkovic et al, 2015; Singh et al, 2013), mice (Marmorstein et al, 2006; Zhang et al, 2010), rats (Marmorstein et al, 2004), dogs (Guziewicz et al, 2013), rhesus monkeys (Gouras et al, 2009), and humans (Dalvin et al, 2015; Mullins et al, 2007). Basolateral plasma membrane localization has also been confirmed in models where Best1 was heterologously expressed, namely Madin-darby canine kidney II cells (Davidson et al, 2011; Davidson et al, 2009; Johnson et al, 2014; Johnson et al, 2013; Milenkovic et al, 2011b) and ARPE-19 cells (Marmorstein et al, 2000; Rosenthal et al, 2006).…”
Section: Best1 Expression Localization and Functionmentioning
confidence: 73%
“…There are small vitelliform lesions (Fig. 4A, B) proximal to the arcades (Boon et al, 2009; Johnson et al, 2015; Marmorstein et al, 2009). Yellowish, subretinal deposits are also common fundus findings (Fig.…”
Section: Clinical Spectrum Of the Bestrophinopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Adenovirus vectors have also been used to deliver BEST1 mutants to iPSC-derived RPE; these studies have defined amino acids needed for channel activity and correct protein localization. 54 iPSC-derived RPE from patients with mutations in the MERTK gene, which causes RP, exhibits defective phagocytosis 55 and from patients with mutations in RP2 shows defects in IFT20 localization, Golgi cohesion, and protein trafficking, which could be corrected either by protein overexpression or by translational read through inducing drugs. 56 iPSC lines from AMD-affected individuals have also been used to derive RPE cells, to model the disease in vitro or for drug screening.…”
Section: Ipsc Retinal Disease Modelingmentioning
confidence: 99%